2020
DOI: 10.31234/osf.io/f6t4g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Political Skill Camouflages Machiavellianism: Career Role Performance and Organizational Misbehavior at Short and Long Tenure

Abstract: On the basis of socioanalytic theory (Hogan & Shelton, 1998) and mimicry-deception theory (Jones, 2014), we hypothesized that political skill would effectively mask Machiavellianism (socioanalytic theory) with consequences for coworker perceived career role performance and actual counterproductive work behavior at low and high levels of job tenure (mimicrydeception theory). We tested our hypotheses in a triangular multisource design in two complementary studies comprised of both target workers and cowo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
0
11
0
2
Order By: Relevance
“…More specifically, Hogan and Shelton (1998) suggested that social skill moderates the relationship between personality and job performance (and other work outcomes). Following this theoretical lineage, a number of studies have investigated the interactive effects of personality and political skill (Blickle et al, 2020;Blickle et al, 2010;Sun and van Emmerik, 2015;Dietl et al, 2017;Kranefeld and Blickle, 2021;Sch€ utte et al, 2018). Indeed, the literature presents a dynamic relation between dispositional or personal ability factors and political skill.…”
Section: Notable Future Research Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Hogan and Shelton (1998) suggested that social skill moderates the relationship between personality and job performance (and other work outcomes). Following this theoretical lineage, a number of studies have investigated the interactive effects of personality and political skill (Blickle et al, 2020;Blickle et al, 2010;Sun and van Emmerik, 2015;Dietl et al, 2017;Kranefeld and Blickle, 2021;Sch€ utte et al, 2018). Indeed, the literature presents a dynamic relation between dispositional or personal ability factors and political skill.…”
Section: Notable Future Research Considerationsmentioning
confidence: 99%
“…Dark side of political skill and will. As a tool to influence the actions of others to support organizational or personal agenda, political skill has also been found to be an effective mechanism to cover self-serving intentions and uncivil behaviors such as deception, abuse and counterproductive work behaviors (Blickle et al, 2020;Clements et al, 2016;Sch€ utte et al, 2018;Zahid et al, 2019). Baloch et al (2017) found that political skill moderated the positive relationship between dark triad personality (narcissism, Machiavellianism and psychopathy) and perceived organizational politics (POPs) given that highly politically skilled individuals with dark triad personality received positive POPs outcomes.…”
Section: Notable Future Research Considerationsmentioning
confidence: 99%
“…This is not only another verification of role theory in the Chinese context but also an enrichment of the antecedent variables of WFC. Moreover, previous studies have examined the positive effect of employees’ PS on their promotion probability [ 21 ], career development [ 50 ] and performance rating [ 93 ]. This study extends the outcome of employee PS by proving the negative effect of PS on WFC.…”
Section: Discussionmentioning
confidence: 99%
“…In supervisor-subordinate interaction, the leader’s needs are often not publicized. Employees high on social astuteness can quickly and accurately understand the leader’s intentions through keen observation [ 50 ]. Moreover, employees with strong abilities in interpersonal influence have good communication skills [ 51 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The political fraudster aims to drain and extract the organization's resources when their duration increases. A political fraudster can hide his global skills in preparation for engaging in selfish and immoral acts for his gain (Blickle et al, 2020).…”
Section: The Concept Of Deceptionmentioning
confidence: 99%